Smart City Research: Contextual Conditions, Governance Models, and Public Value Assessment. (December 2016) - Meijer, Albert J.; Gil-Garcia, J. Ramon; Bolívar, Manuel Pedro Rodríguez
There are three issues that are crucial to advancing our academic understanding of smart cities: (1) contextual conditions, (2) governance models, and (3) the assessment of public value. A brief review of recent literature and the analysis of the included papers provide support for the assumption that cities cannot simply copy good practices but must develop approaches that fit their own situation ( contingency ) and concord with their own organization in terms of broader strategies, human resource policies, information policies, and so on ( configuration ). A variety of insights into the mechanisms and building blocks of smart city practices are presented, and issues for further research are identified.